Evaluasi Penyediaan Air Bersih Dengan Sumber Listrik Tenaga Surya Untuk Fasilitas Umum Desa Pasir Panjang - Muhammad Prihadi Eko Wahyudi; Abdullah Sani; Daniel Sutopo Pamungkas; Sumantri Kurniawan Risandriya; Siti Aisyah; Kamarudin Kamarudin; Nur Sakinah Asaad; Nadrah Wivanius; Rizky Pratama Hudhajanto; Aditya Gautama Darmoyono; Rahmi Mahdaliza; Adlian Jefiza; Ardian Budi Kusuma Atmaja; Arif Wahyu Budiarto; Sakdiah Sakdiah; Bayu Prayogo Setiawan; Indra Daulay; Dodi Radot Lumbantoruan; Michael Paul Smart Simbolon; Anderson Pasaribu; Apriyan Hidayat; Ica Apriana; Nesa Aqila; Geraldo Panjaitan; Qoriatul Fitriyah (Politeknik Negeri Batam, 2022)
In 2018, Batam State Polytechnic has carried out community service in the village of Pasir Panjang, Rempang Island. Pasir Panjang village is one of the villages that is still not electrified by the local electricity company. The village also experiences difficulties in providing clean water because of its location on the coast. Therefore, the dedication of the Department of Electrical Engineering at the State Polytechnic of Batam in the form of grants and installation of water pumps for public facility with an independent power source from a 100WP solar cell. The problem arises when after carrying out the installation, the water pump cannot pump water properly. In the following year, the service was continued by making improvements to the electrical installation system. Starting from the analysis of the causes of system failure to repair. From the analysis and observation, it is known that the cause of the pump not working properly is due to a decrease in voltage because the Rs value in the solar cell system is quite large. By changing the cable size for current distribution, this problem can be resolved.